Levosimendan Reduces Mortality in Adults with Left Ventricular Dysfunction Undergoing Cardiac Surgery: A Systematic Review and Meta‐analysis. Issue 7 (19th May 2015) - Lim, Ju Yong; Deo, Salil V.; Rababa'h, Abeer; Altarabsheh, Salah E.; Cho, Yang Hyun; Hang, Dustin; McGraw, Michael; Avery, Edwin G.; Markowitz, Alan H.; Park, Soon J.
Abstract Introduction Levosimendan is implemented in patients with low cardiac output after cardiac surgery. However, the strength of evidence is limited by randomized controlled trials enrolling a small number of patients. Hence we have conducted a systematic review to determine the role of levosimendan in adult cardiac surgery. Methods PUBMED, WoS, Cochrane database, and SCOPUS were systematically queried to identify original English language peer‐reviewed literature (inception‐October 2014) comparing clinical results of adult cardiac surgery between levosimendan and control. Pooled odds ratio (OR) was calculated using the Peto method; p < 0.05 is significant; results are presented within 95% confidence intervals. Continuous data was compared using standardized mean difference/mean difference. Results Fourteen studies were included in the analysis. Levosimendan reduced early mortality in patients with reduced ejection fraction (5.5% vs. 9.1%) (OR 0.48 [0.23–0.76]; p = 0.004). This result was confirmed using sensitivity analysis. Postoperative acute renal failure was lower with levosimendan therapy (7.4% vs. 11.5%). Intensive care unit stay was shorter in the levosimendan cohort comparable in both groups (standardized mean difference −0.31 [−0.53, −0.09]; p = 0.006; I2 = 33.6%). Levosimendan‐treated patients stayed 1.01 (1.61–0.42) days shorter when compared to control (p = 0.001). Conclusion Our meta‐analysis demonstrates that Levosimendan improves clinical outcomes in patients with left ventricular dysfunction undergoing cardiac surgery. Results of the ongoing multicenter randomized controlled trial are awaited to provide more conclusive evidence regarding the benefit of this drug. doi: 10.1111/jocs.12562 (J Card Surg 2015;30:547–554)